Synthesis and Biological Properties of EGFR-Targeted Photosensitizer Based on Cationic Porphyrin - Yulia S. Bortnevskaya; Nikita A. Shiryaev; Nikita S. Zakharov; Oleg O. Kitoroage; Margarita A. Gradova; Natalia Yu. Karpechenko; Alexander S. Novikov; Elena D. Nikolskaya; Mariia R. Mollaeva; Nikita G. Yabbarov; Natal'ya A. Bragina; Kseniya A. Zhdanova (MDPI AG, 2023)
Photodynamic therapy (PDT) in oncology is characterized by low invasiveness, minimal side effects, and little tissue scarring. Increasing the selectivity of PDT agents toward a cellular target is a new approach intended to improve this method. This study is devoted to the design and synthesis of a new conjugate based on meso-arylporphyrin with a low-molecular-weight tyrosine kinase inhibitor, Erlotinib. A nano-formulation based on Pluronic F127 micelles was obtained and characterized. The photophysical and photochemical properties and biological activity of the studied compounds and their nano-formulation were studied. A significant, 20-40-fold difference between the dark and photoinduced activity was achieved for the conjugate nanomicelles. After irradiation, the studied conjugate nanomicelles were 1.8 times more toxic toward the EGFR-overexpressing cell line MDA-MB-231 compared to the conditionally normal NKE cells. The IC50 was 0.073 ± 0.014 μM for the MDA-MB-231 cell line and 0.13 ± 0.018 μM for NKE cells after irradiation for the target conjugate nanomicelles.